Glycemic, insulinemic and incretin responses after oral trehalose ingestion in healthy subjects. - Chiyo Yoshizane; Akiko Mizote; Mika Yamada; Norie Arai; Shigeyuki Arai; Kazuhiko Maruta; Hitoshi Mitsuzumi; Toshio Ariyasu; Shimpei Ushio; Shigeharu Fukuda; Yoshizane, Chiyo; Mizote, Akiko; et al. (Nutrition Journal, 2017)
Background: Trehalose is hydrolyzed by a specific intestinal brush-border disaccharidase (trehalase) into two glucose molecules. In animal studies, trehalose has been shown to prevent adipocyte hypertrophy and mitigate insulin resistance in mice fed a high-fat diet. Recently, we found that trehalose improved glucose tolerance in human subjects. However, the underlying metabolic responses after trehalose ingestion in humans are not well understood. Therefore, we examined the glycemic, insulinemic and incretin responses after trehalose ingestion in healthy Japanese volunteers.Methods: In a crossover study, 20 fasted healthy volunteers consumed 25 g trehalose or glucose in 100 mL water. Blood samples were taken frequently over the following 3 h, and blood glucose, insulin, active gastric inhibitory polypeptide (GIP) and active glucagon-like peptide-1 (GLP-1) levels were measured.Results: Trehalose ingestion did not evoke rapid increases in blood glucose levels, and had a lower stimulatory potency of insulin and active GIP secretion compared with glucose ingestion. Conversely, active GLP-1 showed higher levels from 45 to 180 min after trehalose ingestion as compared with glucose ingestion. Specifically, active GIP secretion, which induces fat accumulation, was markedly lower after trehalose ingestion.Conclusions: Our findings indicate that trehalose may be a useful saccharide for good health because of properties that do not stimulate rapid increases in blood glucose and excessive secretion of insulin and GIP promoting fat accumulation.